Application of the 5C Principle (Character, Capacity, Capital, Collateral, Condition) as a Credit Risk Mitigation Tool (Case Study on FIFGROUP Sukabumi Branch) - Dini Sri Stania; Heliani (Society : Jurnal Pengabdian Masyarakat, 2026)
The provision of credit to retail finance companies such as FIFGROUP Sukabumi Branch has a strategic role in the economy, but it also carries the risk of bad credit or bad loans that can disrupt business liquidity and profitability. The number of bad credit cases that are often accompanied by violations of fiduciary guarantees, such as embezzlement or illegal diversion of vehicles, are a major problem faced by partners. The purpose of this community service initiative is to evaluate risk mitigation by applying the 5Cs (Character, Capacity, Capital, Collateral, Condition) principles. This will be done using a descriptive qualitative method that uses observation, interviews, and documentation. The results show that the application of the 5C principle serves as a good initial filter to select customer integrity, financial ability, and collateral availability to reduce the risk of default. Overall, combining these five principles has shown that it is critical to keep a company's credit portfolio healthy, protect corporate assets from significant losses, and improve the efficacy of more accurate and responsible credit decision-making.